Enter a problem...
Calculus Examples
f(x)=3x-6f(x)=3x−6 , (0,4)(0,4)
Step 1
The domain of the expression is all real numbers except where the expression is undefined. In this case, there is no real number that makes the expression undefined.
Interval Notation:
(-∞,∞)(−∞,∞)
Set-Builder Notation:
{x|x∈ℝ}
Step 2
f(x) is continuous on [0,4].
f(x) is continuous
Step 3
The average value of function f over the interval [a,b] is defined as A(x)=1b-a∫baf(x)dx.
A(x)=1b-a∫baf(x)dx
Step 4
Substitute the actual values into the formula for the average value of a function.
A(x)=14-0(∫403x-6dx)
Step 5
Split the single integral into multiple integrals.
A(x)=14-0(∫403xdx+∫40-6dx)
Step 6
Since 3 is constant with respect to x, move 3 out of the integral.
A(x)=14-0(3∫40xdx+∫40-6dx)
Step 7
By the Power Rule, the integral of x with respect to x is 12x2.
A(x)=14-0(3(12x2]40)+∫40-6dx)
Step 8
Combine 12 and x2.
A(x)=14-0(3(x22]40)+∫40-6dx)
Step 9
Apply the constant rule.
A(x)=14-0(3(x22]40)+-6x]40)
Step 10
Step 10.1
Evaluate x22 at 4 and at 0.
A(x)=14-0(3((422)-022)+-6x]40)
Step 10.2
Evaluate -6x at 4 and at 0.
A(x)=14-0(3(422-022)-6⋅4+6⋅0)
Step 10.3
Simplify.
Step 10.3.1
Raise 4 to the power of 2.
A(x)=14-0(3(162-022)-6⋅4+6⋅0)
Step 10.3.2
Cancel the common factor of 16 and 2.
Step 10.3.2.1
Factor 2 out of 16.
A(x)=14-0(3(2⋅82-022)-6⋅4+6⋅0)
Step 10.3.2.2
Cancel the common factors.
Step 10.3.2.2.1
Factor 2 out of 2.
A(x)=14-0(3(2⋅82(1)-022)-6⋅4+6⋅0)
Step 10.3.2.2.2
Cancel the common factor.
A(x)=14-0(3(2⋅82⋅1-022)-6⋅4+6⋅0)
Step 10.3.2.2.3
Rewrite the expression.
A(x)=14-0(3(81-022)-6⋅4+6⋅0)
Step 10.3.2.2.4
Divide 8 by 1.
A(x)=14-0(3(8-022)-6⋅4+6⋅0)
A(x)=14-0(3(8-022)-6⋅4+6⋅0)
A(x)=14-0(3(8-022)-6⋅4+6⋅0)
Step 10.3.3
Raising 0 to any positive power yields 0.
A(x)=14-0(3(8-02)-6⋅4+6⋅0)
Step 10.3.4
Cancel the common factor of 0 and 2.
Step 10.3.4.1
Factor 2 out of 0.
A(x)=14-0(3(8-2(0)2)-6⋅4+6⋅0)
Step 10.3.4.2
Cancel the common factors.
Step 10.3.4.2.1
Factor 2 out of 2.
A(x)=14-0(3(8-2⋅02⋅1)-6⋅4+6⋅0)
Step 10.3.4.2.2
Cancel the common factor.
A(x)=14-0(3(8-2⋅02⋅1)-6⋅4+6⋅0)
Step 10.3.4.2.3
Rewrite the expression.
A(x)=14-0(3(8-01)-6⋅4+6⋅0)
Step 10.3.4.2.4
Divide 0 by 1.
A(x)=14-0(3(8-0)-6⋅4+6⋅0)
A(x)=14-0(3(8-0)-6⋅4+6⋅0)
A(x)=14-0(3(8-0)-6⋅4+6⋅0)
Step 10.3.5
Multiply -1 by 0.
A(x)=14-0(3(8+0)-6⋅4+6⋅0)
Step 10.3.6
Add 8 and 0.
A(x)=14-0(3⋅8-6⋅4+6⋅0)
Step 10.3.7
Multiply 3 by 8.
A(x)=14-0(24-6⋅4+6⋅0)
Step 10.3.8
Multiply -6 by 4.
A(x)=14-0(24-24+6⋅0)
Step 10.3.9
Multiply 6 by 0.
A(x)=14-0(24-24+0)
Step 10.3.10
Add -24 and 0.
A(x)=14-0(24-24)
Step 10.3.11
Subtract 24 from 24.
A(x)=14-0(0)
A(x)=14-0(0)
A(x)=14-0(0)
Step 11
Step 11.1
Multiply -1 by 0.
A(x)=14+0⋅0
Step 11.2
Add 4 and 0.
A(x)=14⋅0
A(x)=14⋅0
Step 12
Multiply 14 by 0.
A(x)=0
Step 13
